A progression analysis of motor features in Parkinson's disease based on the mapper algorithm - Ma, Ling-Yan; Feng, Tao; He, Chengzhang; Li, Mujing; Ren, Kang; Tu, Junwu (Frontiers in Aging Neuroscience, 2023)
Background. Parkinson’s disease (PD) is a neurodegenerative disease with a broad spectrum of motor and non-motor symptoms. The great heterogeneity of clinical symptoms, biomarkers and neuroimaging and lack of reliable progression markers present a significant challenge in predicting disease progression and prognoses. Methods. We propose a new approach to disease progression analysis based on the mapper algorithm, a tool from topological data analysis. In this paper, we apply this method to the data from the Parkinson’s Progression Markers Initiative (PPMI). We then construct a Markov chain on the mapper output graphs. Results. The resulting progression model yields a quantitative comparison of patients’ disease progression under different usage of medications. We also obtain an algorithm to predict patients’ UPDRS III scores. Conclusions. By using mapper algorithm and routinely gathered clinical assessments, we developed a new dynamic models to predict the following year’s motor progression in the early stage of PD. The use of this model can predict motor evaluations at the individual level, assisting clinicians to adjust intervention strategy for each patient and identifying at-risk patients for future disease-modifying therapy clinical trials.